Principles of information security - Whitman, Michael E., 1964-; Mattord, Herbert J. (Australia : Cengage Learning, 2018)
"Taking a managerial approach, this bestseller emphasizes all aspects of information security, rather than just a technical control perspective. You receive a broad overview of the entire field of information security and related elements with the detail to ensure understanding. You review terms used in the field and a history of the discipline as you learn how to manage an information security program. Current and relevant, this edition highlights the latest practices with fresh examples that explore the impact of emerging technologies, such as the Internet of Things, Cloud Computing, and DevOps. Updates address technical security controls, emerging legislative issues, digital forensics, and ethical issues in IS security, making this the ideal IS resource for business decision makers." -- Provided by publisher.
Introduction to information security -- The need for security -- Legal, ethical, and professional issues in information security -- Planning for security -- Risk management -- Security technology: access controls, firewalls, and VPNs -- Security technology: intrusion detection and prevention systems, and other security tools -- Cryptography -- Physical security -- Implementing information security -- Security and personnel -- Information security maintenance.
Includes bibliographical references and index.
Keywords: Computer networks -- Security measures; Computer security